INTERN RÖRLIGHET : En kvalitativ studie om organisationers arbete med att tillvarata kompetens - Isaksson, Matilda (Luleå tekniska universitet, Samhällsvetenskap, 2022)
A hot topic right now is how organizations could succeed in taking advantage of the qualification they have internally due to a large mobility in the labor market. This is an issue that often appears in organizations' governing documents, but many organizations lack methods to work by. In this study, the work of four organizations was examined to utilize the qualification from an organizational perspective to be able to make suggestions for improvement to Luleå municipality. To be able to provide adequate proposals to Luleå municipality, organizations in various sectors of society have been studied. To analyze the empirical data, Anttila, Lindelöw and Lindmark and Önnevik's reasoning regarding qualification supply have been used. The research method used was qualitative with anabductive approach and is based on five interviews. The qualitative method was used to gain a deeper understanding of the experiences described by the interviewees. It can be stated that all organizations strive to offer internal mobility. The results, however, showed that none of the surveyed organizations has a policy for internal mobility. The conclusions that can be drawn are that it is difficult to increase internal mobility due to lack of documentation and insufficient descriptions of the work. The most interesting finding was that there were different definitions of the concept of internal mobility between organizations. The study shows that there were shortcomings in the strategic work in terms of making use of qualification.